Analisis Kinerja Alat Penukar Kalor Jenis Shell and Tube Pendingin Aliran Air pada PLTA Jatiluhur - Handoyo, Yopi; ., Ahsan (Jurnal Energi Dan Manufaktur; Vol 5 No 1 (2012): Oktober 2012)
This paper presented a shell and tube heat exchanger with type BFU, that is by making its performance analysis. Result of this evaluation will be compared to appliance with performance prediction heat exchanger second with type BFS, besides result of the prediction will be compared to result of examination of second type which done by in PLTA JATILUHUR. This analysis require to be done by because heat exchanger with type of BFU often happened leakage especially at rear head because at the shares quickly happened conglomeration of deposit. The detailed design on heat exchanger components was done based on Standards of Tubular Exchanger Manufacturers Association (TEMA). The heat exchanger type that was chosen is BFS type with two shell and two tube passes. According to the chosen heat exchanger geometry, the fluid flow in shell side was analyzed by CFD software to find flow pattern and properties of this fluid. The result of fluid flow analysis with CFD software is accurate enough or close to the theoretical analysis result. Therefore, it is important to analyze fluid flow along the shell in different surface of cross section with certain spacing to find completed conditions of fluid. More detailed design and analysis of heat exchanger is needed to have a heat exchanger design that can be fabricated and have good performance.
Keywords: Conglomeration of deposit, heat exchanger, fouling